Morphological and Molecular Characterization of Three New Records of Ostracod Species in Kurdistan Region - Latef, Berivan Asaad; Ali, Luay Abdul-Qadir (Zanco Journal of Pure and Applied Sciences, 2025)
Research on Ostracod identification in Iraq is currently limited, specifically in Erbil Province with relatively few studies conducted on this topic. As a result, there is a significant knowledge gap regarding the diversity and distribution of ostracod species within the country. This study fills significant gaps by study the morphology and molecular analysis of three novel ostracoda species which are (Stenocypris hislopi, Cypridopsis vidua and Candona neglecta), that belong to two families (Cyprididae and Candonidae), collected from 17 different sites in boundary Erbil Province, during September 2021 to October 2022. For biological analysis, a number of aquatic plants, green algae, and zooplanktonic net were used. Meanwhile, some physical and chemical parameters were taken. Following a comprehensive morphological study, the PCR product of the COI gene was subjected to sequencing, and the resulting sequences were deposited in the GenBank database under unique accession numbers. Subsequently, phylogenetic analysis was conducted, leading to the identification of the examined species, which are now being reported from the Kurdistan region. This study focused on molecular inquiry besides morphology identification. This finding implies that molecular methods ought to be used in subsequent biodiversity studies in order to assess species diversity accurately.